Metastable interstitials in CdSe and CdS crystals - Borkovska, L.V.; Bulakh, B.M.; Khomenkova, L.Yu.; Korsunska, N.O.; Markevich, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
An "anomalous" defect drift in external electric field, namely, transport of acceptorlike centres from the anode to the cathode, has been observed in CdS:Cu, CdS:Ag and nominally undoped CdSe crystals at 350-700 K. The effect is accounted for by transformation of acceptors into donors under heating. The donors are metastable centres that do not display themselves in the equilibrium state and can be revealed only by drift in electric field. The acceptors are shown to be substitutional impurity atoms, acceptor-to-donor transformation occurring due to transition of these atoms from lattice sites to interstitials. Under cooling reverse donor-to-acceptor transition takes place.